Efektivitas Sistem Layanan Payroll Dalam Pembayaran Tunjangan Kinerja Bagi Anggota POLRI di Lingkungan POLDA Bengkulu - Aprianty, Henny; Arnubi, Arnubi; Sakti, Budiman; Purnawan, Heru (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2024)
This research was conducted with the aim of finding out the effectiveness of the payroll service system in paying performance allowances for police members within the Bengkulu Regional Police. The type of research used in this thesis is qualitative research. This research uses descriptive case study techniques, which are carried out intensively, in detail and in depth on the research object. The data in this research was obtained from primary data and secondary data. Data collection techniques used are observation methods, interview methods, and documentation methods. The data analysis technique is using Data Reduction, Data Display (Data Presentation), and Conclusion Drawing/Verification. The results of this study indicate that: 1). The effectiveness of the payroll service system in paying performance allowances for police members within the Bengkulu Regional Police has been implemented well and responsibly, seen from program effectiveness indicators which include: a) Indicators of Accuracy of Program Targets, b) Indicators of Program Socialization, c) Indicators of Achievement of Program Goals, and d) Program Monitoring Indicators. 2). The members of the National Police and ASN who are involved have also tried their best to continue to improve the effectiveness of the payroll service system in paying performance allowances for police members within the Bengkulu Regional Police.